DEVELOPMENT OF THE AUTOMATIC METHOD OF ADJUSTING LAVAL NOZZLE PARAMETERS AND ITS SIMULATION ALGORITHM - MYKHAILIUK, VASYL; GÓRAL , TOMASZ; PROTSIUK, VASYL; DEINEHA, RUSLAN; FAFLEI, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2024)
One of the methods of cooling gas flows is the use of a Laval nozzle - a device in which the gas flow is accelerated to speeds that exceed the speed of sound. However, during the operation of such a nozzle, the gas flow is very sensitive to changes in the cross-section of the opening. For example, to change the Mach number (M) by 10% (from M=0.9 to M=1), it is enough to change the cross-sectional area by 1%, and to change from M=0.95 to M=1 – by 0.25 %. Various methods and equipment are used to change the gas dynamic parameters in the Laval nozzle, but they usually apply to gas turbine engines. The use of similar methods and equipment for cooling the gas flow of small volumes is impractical and practically impossible. A Laval nozzle made of silicone or rubber can be used to change the gas and thermodynamic parameters of the flow. In the paper, the gas and thermodynamic parameters of the gas flow passing through the nozzle were investigated. For this, its three-dimensional model was created and simulation modeling was applied. During modeling, the composition of gases, as well as pressures and temperatures at the nozzle inlet and outlet are taken into account. It is established that the maximum Mach number in the nozzle reaches 1.53, while the gas temperature decreases from 120 °C to 75 °C. The study also showed an uneven distribution of pressure on the inner surfaces of the nozzle, which affects its stress-deformed state. In order to be able to adjust the parameters of the Laval nozzle, an automated method is proposed, which is based on the change of the smallest cross-section depending on the pressure, which allows maintaining the required gas flow rate and reducing the temperature. The nozzle is made of hyperelastic materials that can withstand high temperatures and are resistant to wear. For the design of nozzles with automated regulation, a simulation modeling algorithm has been developed, which allows studying the stress-strain state of the nozzle, taking into account the change in pressure on its inner surface. The results of the simulated simulation according to the developed algorithm showed the maximum stress (0.33 MPa) and displacement (0.48 mm) in the area of the smallest diameter of the nozzle. Further research involves optimization of the design of the Laval nozzle using parametric optimization to achieve the best efficiency of its operation.